Edukasi Tindakan Pencegahan Penyakit Infeksi bagi Petugas Kebersihan Terkait Pandemik Covid-19 - Mulyanti Roberto Muliantino; Yuanita Ananda; Boby Febri Krisdiyanto; Leni Merdawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
Cleaning workers was one of high risk workers in Covid-19 infection who exposed to garbage from individuals, households and business waste every day. During Covid-19 pandemic there was increased disposal of infectious waste such as masks and gloves from households without sorting process which increasing risk of infection for cleaning workers. Preventive effort of cleaning workers was needed as vigilance in daily activities. Therefore, an education was carried out about prevention of infectious disease related Covid-19 pandemic to improving knowledge and understanding of cleaning workers as preventive measure. Education program was carried out to 50 cleaning workers in Environmental Department of Padang on 29-30 June 2020. Modules, videos, and demonstrations procedures of hand washing, mask and glove using were used in these educations. Education program consist of basic concepts and preventive measures against infectious disease related Covid-19 pandemic. The results showed there was increased knowledge of cleaning workers about preventive way against infectious disease related Covid-19 pandemic after participating in education program.